Vesical Calculi with Utero Cervico Vaginal Prolapse - Chhabra, S.; Raman, Shweta (Global Journal of Medical and Clinical Case Reports, 2014)
Vesical calculi are not commonly seen with utero vaginal prolapse. Calculi may be missed unless ultrasonography or X-ray is done. If not diagnosed problems can occur during surgery and post operatively. If vesical calculi are removed vaginally during anterior colporrhaphy, it may lead to fistula formation. Suprapubic cystotomy and removal of calculi done during vaginal surgery for genital prolapse seems better option. We present 3 cases which were managed within a span of 6 months with satisfactory results.